Lung cancer adrenal gland metastasis: Optimal fine‐needle aspirate and touch preparation smear cellularity characteristics for successful theranostic next‐generation sequencing. Issue 11 (15th July 2014) - Gleeson, Ferga C.; Kipp, Benjamin R.; Levy, Michael J.; Voss, Jesse S.; Campion, Michael B.; Minot, Douglas M.; Tu, Zheng J.; Klee, Eric W.; Lazaridis, Konstantinos N.; Kerr, Sarah E.
Abstract : BACKGROUND: Multigene molecular testing to guide personalized therapy for oncology patients is of increasing clinical relevance. Molecular testing of fine‐needle aspiration samples is underused, but when acquired with minimally invasive techniques could become the standard of care to obtain theranostic specimens. The aims of the current study were to identify key cytology specimen selection criteria suitable for next‐generation sequencing (NGS) and to determine the prevalence and spectrum of pathogenic alterations in a cohort of patients with AJCC stage IV lung cancer. METHODS: A total of 70 adrenal gland cytology specimens with direct smears were screened to identify 56 patients with a single slide containing at least 300 total cells and 20% tumor nuclei. After DNA extraction, the NGS protocols were used to simultaneously detect mutations in >2800 exonic regions in 50 key cancer genes. RESULTS: A total of 28 specimens produced acceptable NGS results. Specimens with a combined critical cell mass (>5000 viable cells) and a DNA concentration >5 ng/µL resulted in a 95% chance of successful sequencing. A total of 37 pathogenic alterations were identified in 10 genes and in 25 patients (85%). A pathogenic alteration (≥1) linked to available or developing targeted therapies was revealed in 50% of cases. CONCLUSIONS: The data from the current study demonstrate that theranostic NGS can be applied to adrenal gland metastasis using routine cytologic smear specimens. The characteristics of such smears could be evaluated during onsite adequacy assessment by cytopathology professionals. This model greatly augments the opportunity for customized genotype‐directed therapy from minimally invasive techniques. Cancer (Cancer Cytopathol) 2014;122:822–832. © 2014 American Cancer Society . Abstract : Cellular cytologic smears from adrenal gland metastases are suitable for next‐generation sequencing in patients with advanced lung cancer. In the current study, the characteristics of acceptable smears are outlined for use in onsite adequacy evaluation.